Local Surface Structure and Composition Control the Hydrogen Evolution Reaction on Iron Nickel Sulfides. Issue 15 (9th March 2018) - Bentley, Cameron L.; Andronescu, Corina; Smialkowski, Mathias; Kang, Minkyung; Tarnev, Tsvetan; Marler, Bernd; Unwin, Patrick R.; Apfel, Ulf‐Peter; Schuhmann, Wolfgang
Abstract: In order to design more powerful electrocatalysts, developing our understanding of the role of the surface structure and composition of widely abundant bulk materials is crucial. This is particularly true in the search for alternative hydrogen evolution reaction (HER) catalysts to replace platinum. We report scanning electrochemical cell microscopy (SECCM) measurements of the (111)‐crystal planes of Fe4.5 Ni4.5 S8, a highly active HER catalyst. In combination with structural characterization methods, we show that this technique can reveal differences in activity arising from even the slightest compositional changes. By probing electrochemical properties at the nanoscale, in conjunction with complementary structural information, novel design principles are revealed for application to rational material synthesis. Abstract : Small change, big difference : Local investigation of the hydrogen evolution reaction (HER) on a single crystal of iron nickel sulfide, one of the most active non‐noble‐metal HER catalysts, was carried out using scanning electrochemical cell microscopy (SECCM). Small variations in the Ni/Fe ratio at the surface induce tremendous changes in the catalytic HER activity.